PUBLIC-PRIVATE PARTNERSHIP IN KAZAKHSTAN: PROBLEMS AND PROSPECTS - G. Nyurlikhina; R. Salimbayeva; Zh. Oralbayeva; B. Beknazarov; K. Nurgaziyev (Academic Journal of Physical and Chemical Sciences, 2019)
The article is devoted to the analysis of the development of public-private partnerships in the Republic of Kazakhstan. The assessment of the formed regulatory framework in the field of public-private partnership projects is given. The features of the implementation of public-private partnership projects in Kazakhstan are identified, the roles of the parties involved in them are indicated. The analysis of PPP projects in the regional context was carried out according to such indicators and criteria as the number of projects, the amount of financing, the ratio of attracted investments to government obligations for financing PPP projects, coverage of areas and sectors of the economy, development dynamics. The results of the analysis allowed the authors to highlight the strengths and weaknesses of the development of PPPs in each region of Kazakhstan. The conclusion is drawn about the extremely uneven development of PPP in the regions of the Republic of Kazakhstan. The inability of most PPP projects to reduce the overall burden on the country’s budget is indicated as an unfavorable trend in Kazakhstan’s practice of developing PPPs - in fact, they only allow deferring payments from the budget. Positive assessment of the transformation of the legislation of the Republic of Kazakhstan in the field of PPPs, the authors substantiate the need to create a more favorable and safe investment climate for more active involvement of the private sector in PPP projects.